ダイ41ジ ナンキョク チイキ カンソクタイ エットウ ホウコク 2000-2001 - 渡邉, 研太郎; ワタナベ, ケンタロウ; Watanabe, Kentaro (2009)
P(論文) 第41次南極地域観測越冬隊(第41次越冬隊)は40名で構成され,全員が昭和基地で越冬し,所期の観測をほぼ実施して2001年3月28日,全員無事帰国した.2000年2月1日,第40次越冬隊より基地運営を引継ぎ,翌2001年2月1日に第42次越冬隊へ引き継ぐまでの間,第V期5カ年計画の4年次にあたる観測・設営活動を実施した.設営活動は,昭和基地整備計画(10カ年計画)の9年次として計画された,夏期隊員宿舎の増設,設備更新を主としたものだった.観測系ではみずほ基地滞在による吹雪観測,航空機による基地上空の大気採集や内陸大気観測等を行い,やまと山脈域での隕石探査では50 kgを超す鉄隕石を含む3554個の隕石を採集した.予想外の出来事としては試験的に持ち込んだ10 kWの風力発電装置が7月初頭の大型ブリザードにより倒壊したほか,12月中旬に発電棟内の燃料タンクから軽油が棟外へ漏れる事故があった. The wintering party of the 41st Japanese Antarctic Research Expedition (JARE 41), consisting of 40 members who overwintered at Syowa, carried out most of the planned scientific observations and returned home safely on 28 March 2001. From February 1st 2000, when JARE-41 took over management of Syowa Station from JARE-40, until February 1st 2001, when JARE-41 handed it over to JARE-42, it conducted scientific observations and logistic programs as the fourth year in the 5th five-year plan of JARE. The logistic program consisted mainly of construction work for expansion of a summer party lodging and replacement of facilities. This work was the 9th year of a 10-year plan for maintenance of facilities at Syowa Station. Research activities including snowstorm observations during a stay at Mizuho Station, air-borne collection of air over Syowa, air-borne surveys of the inland atmosphere and collection of 3554 meteorites, including an iron meteorite more than 50 kg in weight, in the Yamato Mountains. Unexpected incidents included collapse of a newly built 10 kW wind generator test plant during a big blizzard in early July, and a leak of diesel oil from a tank in a generator building at Syowa Station in mid-December. departmental bulletin paper